Doing better with less energy [fuel-efficient power generation]. - Sathbye, J.
The authors describe how many fuel-efficient coal-fired power generation technologies can be adopted at reduced net cost, but argue that, unless barriers to innovation are removed, their adoption will be far from automatic
Keywords: Coal-fired power generation; Fuel-efficient generation; Generation cost; Steam power plants